Lone survivor [videorecording (DVD)] - Berg, Peter, 1964-; Wahlberg, Mark, 1971-; Foster, Ben, 1980-; Hirsch, Emile, 1985-; Bana, Eric; Kitsch, Taylor, 1981- (Universal Studios Home Entertainment, 2014)
The story of four Navy SEALs sent on an ill-fated covert mission to neutralize a high-level Taliban operative. They are ambushed by enemy forces in the Hindu Kush region of Afghanistan. Based on The New York Times bestseller.